Ionic framework constructed with protic ionic liquid units for improving ammonia uptake. Issue 36 (6th April 2021) - Li, Jiaran; Luo, Li; Yang, Le; Zhao, Chaoyang; Liu, Yibang; Wu, Zhixin; Luo, Xiaoyan; Lin, Jinqing
Abstract : A [Ph3ImH][Tf2 N]2 framework constructed from ionic liquid units frustrated with ammonia presents high reversible ammonia uptake of 13.53 mmol g −1 . Abstract : In this work, an ionic framework [Ph3ImH][Tf2N]2 constructed from protic imidazolium ionic liquid units through ionic and hydrogen bonding interactions was synthesized for selective ammonia uptake. Investigation of the NH3 uptake mechanism indicates that the acid sites in [Ph3ImH][Tf2 N]2 would be frustrated when contacted with NH3, and the frustration of [Ph3ImH][Tf2 N]2 precipitates NH3 capture by hydrogen bonding and physical interactions, and the NH3 could be released under mild conditions. There was no obvious decrease in capacity over 10 consecutive cycles of ammonia uptake and release.